A study of African postcolonial and post-apartheid challenges: a legacy of ineptitude? - Makhudu, P. K. D. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
Postcolonial African states have gained notoriety for what most of the literature suggests intractable problems in the running, control and management of Africa’s material and human resources. Quite often the litany of ills and imperfections laid at the feet of African leaders and governments appear so colossal that few solutions are countenanced. The recent social upheavals and civil wars in Cameroon, Somalia, Nigeria, Sudan, Uganda as well as in north African states like Egypt, Libya and Tunisia suggest that severely dislocated societies can hardly be effectively rescued or expeditiously repaired in an unstructured way or as consequent to a misconception of democracy, poor governance and poor leadership with a predilection for corruption. In other words, Africa’s collective woes have always been judged as owing to managerial ineptitude. The proposition here is that analysis of governance and administrative practices in Botswana and South Africa could reveal that the social and political challenges are being tackled in innovative and strategic ways. The reasons for that have more to do with the socio-economic mechanisms created by the elite classes and transnational corporations in those societies. In a way, the postcolonial and post-apartheid ways and means of in the two countries owe their stability and partial successes to the structures put in place by the former colonial upper classes. The present leadership and political groupings are in actuality a recapitulation of the governance and control mechanisms of colonial and apartheid times. The legacy of ineptitude reigning in many African countries is due to an inability of the ruling elites to adopt and adapt the well-laid ways and means of the colonial masters and their transnational corporations. As such, the ineptitudes are hardly innately African, but rather are part of the groundwork laid by undemocratic practices of the past and present globalised corporations.
Journal article, published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Governance; Ineptitude; Postcoloniality; Government Resources management; Postcolonialism; Post-apartheid era